Social Adapter Model: Development of Coastal Resources Potential Through Empowerment of Coastal Communities in Watu Pecak Beach Lumajang District - Affroh Try Febri Kurniawati; Yayuk Yuliati; Edi Susilo (HABITAT, 2021)
Coastal areas and their natural resources have an important meaning for the economic development of the Indonesian people. This is reflected in the East Java region, which is one of the provinces rich in natural resources, both in the form of minerals and fishery products. For example in the area of Watu Coast Pecak there is potential for natural resources such as Pasir Pantai which has good quality sand for house building and this is an attraction for itself to develop. The purpose of this study was to identify the implementation of the management of Watu Pecak Beach in developing coastal resource potential at Watu Pecak Beach, identifying the role of stakeholders in the management of Watu Pecak Beach, analyzing the activities of the WatuPecak Coast community in utilizing coastal resources available at Watu Pecak Beach, and designed a Social Adapter Model for the development of coastal resource potential in Watu Pecak Beach. The data analysis used in this study used a qualitative descriptive method. The results showed that the implementation of the management of Watu Pecak Beach was still not optimal. The role of stakeholders in implementing Watu Pecak Beach is still not fully active because it is still constrained by administrative permits. The activities of the coastal communities of Watu Pantai Pecak have a variety of activities. The design of this ring circumference social adapter model is used as a frame to strengthen the institutions of coastal communities in Watu Pecak Beach.